2019
DOI: 10.1001/jamadermatol.2019.3236
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Complete Remission After Rituximab Therapy for Pemphigus

Abstract: IMPORTANCE Rituximab has emerged as a front-line therapy for pemphigus, but prognostic factors for achieving complete remission off therapy (CROT) with oral systemic agents remain unknown. OBJECTIVES To describe rates of CROT and relapse and identify prognostic factors for achieving CROT after rituximab therapy for pemphigus. DESIGN, SETTING, AND PARTICIPANTS A single-center, retrospective, cohort study was conducted at the University of Pennsylvania including 112 patients with pemphigus treated with rituximab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
43
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 28 publications
3
43
3
2
Order By: Relevance
“…All but six patients included in our study received this drug as the last‐line therapy for disease refractory to conventional immunosuppressive regimens. The CR rate after the first rituximab cycle was 73%, which is very close to 77% CR rate calculated for high‐dose rituximab regimens by Wang et al 3 or 71% recently reported by Kushner et al 6 A recent randomized controlled prospective study suggested that rituximab given as the first‐line therapy produces even better results with the CRoff rate of 89% at 24 months, supporting an early use of this drug in pemphigus 4 . In fact, all six patients in our cohort who received rituximab as the first‐line therapy also achieved CR.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…All but six patients included in our study received this drug as the last‐line therapy for disease refractory to conventional immunosuppressive regimens. The CR rate after the first rituximab cycle was 73%, which is very close to 77% CR rate calculated for high‐dose rituximab regimens by Wang et al 3 or 71% recently reported by Kushner et al 6 A recent randomized controlled prospective study suggested that rituximab given as the first‐line therapy produces even better results with the CRoff rate of 89% at 24 months, supporting an early use of this drug in pemphigus 4 . In fact, all six patients in our cohort who received rituximab as the first‐line therapy also achieved CR.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, most reports published long-term follow-up covering a time span of only about three years after the first rituximab therapy. 6,[8][9][10][11][12][13] In the current study, we sought to examine response and relapse rates in pemphigus patients followed for a considerably longer period of time. We, therefore, included only patients who continuously remained in our care for at least 36 months after the first rituximab cycle, yielding a median follow-up of 104 months (eight years and eight months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the letter published by Muntyanu et al, which highlighted the recent study from Kushner et al 1 Based on this paper, they suggested that the use of the lymphoma regimen (LR) for rituximab (RTX) could be considered in our practice to increase the rate of complete remission off therapy (CROT) in pemphigus patients.…”
mentioning
confidence: 99%
“…Kushner et al published the largest study to date exploring the efficacy of rituximab in PV/PF and predictors of response. 2 This single-center, retrospective, cohort study conducted from 2005 to 2016, included 96 PV and 16 PF patients. The primary end-point was complete response off therapy (CROT) after 1 cycle of treatment and factors associated with favorable response.…”
mentioning
confidence: 99%